The Co-Movement of China and US Stock Indices: A Portfolio Diversification Analysis - Abdullah, Ahmad Monir; Abdul Wahab, Hishamuddin; Mohammed Masih, Abul Mansur; Abdul Majid, Mariani; Wong, Wai-Yan (Universiti Utara Malaysia Press, 2023)
The aim of this article is to find diversification opportunities by examining the time-varying and time-scale-based volatility and correlation of the US and Chinese stock market indices with crude oil, gold and Bitcoin price returns, as well as the exchange rate of the Chinese Yuan Renminbi against the US Dollar (CNY/USD) using a vector error correction model (VECM), namely, maximum overlap discrete wavelet transformation (MODWT). Furthermore, individual and institutional investors may also reduce the risk of their investment portfolio by investing in commodities and stock markets from countries with a negative or substantially low correlation. Our VECM result shows that Bitcoin, crude oil and CNY/USD lead the other variables under consideration, indicating that changes in the prices of Bitcoin, crude oil and CNY/USD affect the US and Chinese stock market indices, as well as gold. Our research utilising the MODWT technique shows that Bitcoin leads crude oil at almost all levels, indicating that crude oil prices will respond to Bitcoin price movement in the long and medium term. However, investors may be deterred from using Bitcoin as a diversification tool due to its extreme volatility. The research also indicates that diversification with gold may help US investors. However, the continuous wavelet transformation finding shows that the diversification benefit effects will persist for a holding period of little more than 64 days. Our study results tend to emphasise the significance of using reasonably modern methods to identify diversification possibilities for investors with diverse investment horizons or holding stocks for various periods.